SELF-OSCILLATING PARAMETRIC PRESSURE SENSORS - OSADCHUK, Jaroslav; OSADCHUK, Alexander; OSADCHUK, Vladimir (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Self-oscillating parametric pressure sensors are proposed based on transistor microelectronic structures with negative differential resistance with primary strain-sensing resistor and diode, and the primary strain-sensing elements are active elements of the self-oscillator circuit, which simplifies the design of pressure sensors. It is also proposed to replace the passive inductance of the self-oscillator oscillatory circuit with an active inductive element based on a transistor with a phase-shifting RC circuit, which makes it possible to expand the range of output frequency adjustment, as well as to fully produce pressure sensors using microelectronic technology. Based on the consideration of physical processes in primary strain-sensing elements and self-oscillators, mathematical models of pressure sensors have been developed, on the basis of which parametric dependences of the conversion and sensitivity functions have been obtained. It is shown that the main contribution to the change in the conversion function is made by the change in pressure. This causes a change in the equivalent capacitance and negative differential resistance of the oscillatory system of sensor self-oscillators, which in turn changes the output frequency of the devices. The sensitivity of the pressure sensors varies from 0.365 kHz/kPa to 2.45 kHz/kPa when the pressure changes from 0 kPa to 2050 kPa. The obtained parametric dependences of the conversion functions of pressure sensors show the possibility of easier calculation of the main characteristics of the sensors and clearly show the influence of each parameter of the primary converters and the parameters of the self-oscillator on the output frequency of the sensors in comparison with the calculations of the conversion functions based on the Kirchhoff equations. Pressure sensors with a frequency output do not require analog-to-digital converters and amplifying devices for further processing of information signals, which reduces the cost of information-measuring equipment, in addition, it is possible to transmit information over a distance when the sensors operate at microwave frequencies.
Keywords: sensor; pressure; negative differential resistance; self-oscillator; strain-sensing resistor; strain-sensing diode